Choreographing “Sunset at Noon?” Towards the Exploration of a Theatre of “Shufflism”. - Emoruwa, Felix Damilola (NIU Journal of Humanities; Vol 9 No 2 (2024): NIU Journal of Humanities, Vol. 9 No. 2, June 2024DO - 10.58709/niujhu.v9i2.1921, 2024)
Live theatre practice in Nigeria is arguably suffering from the effects of poor documentation of the wonderful experimental feats practitioners have stumbled upon in the course of their relentless search to push forward the frontiers of theatre practice. Scholars have therefore at best struggled to fit such works (for the few that have been attempted) within the tenets and norms of established theater traditions and conventions of old. This paper has attempted in the face of the many performance poetics that gave credence to the cultures and emerging cultures in music, dance, drama and the technical theatre idioms that gave identities to experimental tendencies wrapped in the traditions of postmodernism, globalization, hybridism, etc, to give scholarly voice to one of such brilliantly put together experimental bid haven come into existence since 2004. Shufflism that is pushed forward as a new radically postulated theatre tradition in this paper was a product of an experimental class by the 2004/2005 M.A class of the Performing Arts students of Unilorin, Nigeria through the production of their play ‘Sunset at Noon?’. The paper discovers amongst other things that the tenets that are linked to the new theatre approach are new, original and creative innovations and approaches that suited the cause to which they were set. The paper is both descriptive and analytical of the content and context that gave birth to the new theatre tradition. It is therefore hoped that the paper will generate reactions and counter reactions that will not only give deserving voices to the articulation and spread of this brilliant theatre tradition, but others also which has suffered stunted growth over the years like it shall be liberated.         Keywords: Choreography, Sunset, Shufflism, Exploration, Theatre.